2009
DOI: 10.1002/rcm.3911
|View full text |Cite
|
Sign up to set email alerts
|

G‐SIMS: relative effectiveness of different monatomic primary ion source combinations

Abstract: An analysis is made of the characteristics of monatomic primary ion sources to generate G-SIMS (gentle SIMS) spectra. In previous studies, this is resolved into the parameter beta that describes the relative intensities of ions in the series C(n)H(n+2-i) as i changes. For this, data from polystyrene are most extensive. It is found that the experimental beta values, which relate to the emitted secondary ion fragment surface plasma temperatures, are accurately described by an empirical fit involving the ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In 2000, Gilmore and Seah established the G-SIMS technique 5 which showed that the spectra for different primary ion sources were related and that the way that spectra changed from source-to-source depended on the source and its ion impact energy. 6 Later, it was shown 7 that secondary ion spectra from Irganox 1010 for Ar + , Bi + , Bi 3 + , and Bi 5 + primary ion sources could all be related, over many orders of magnitude, to an accuracy of 2.3% for 389 fragment peaks. These spectra involved the product of just two spectra, one representing a low degree of fragmentation and one a high degree.…”
Section: Introductionmentioning
confidence: 99%
“…In 2000, Gilmore and Seah established the G-SIMS technique 5 which showed that the spectra for different primary ion sources were related and that the way that spectra changed from source-to-source depended on the source and its ion impact energy. 6 Later, it was shown 7 that secondary ion spectra from Irganox 1010 for Ar + , Bi + , Bi 3 + , and Bi 5 + primary ion sources could all be related, over many orders of magnitude, to an accuracy of 2.3% for 389 fragment peaks. These spectra involved the product of just two spectra, one representing a low degree of fragmentation and one a high degree.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if the intensity ratios, F 12,i of two spectra, I(1,m/z) and I(2,m/z) were plotted, it was seen that the data exhibit linear regions when F 12,i is plotted on a log 10 scale. This was interpreted to show that 21,22 where β* is given by † Part of the Barbara J. Garrison Festschrift. * To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using many different primary ions have been made using polystyrene, (CH 2 -CHPh) q , where Ph is a pendant phenyl ring and q shows the number of repeat groups or the degree of polymerization. 21,23 The spectra are referenced to that for argon at 7 keV beam energy and values of β () 0.431β*) 22 can then be measured. In polystyrene, in the mass range 12 e m/z e 160 u, for which 1 e j e 12 and for 0 e i e 10, it is found that β is effectively constant.…”
Section: Introductionmentioning
confidence: 99%
“…The G‐SIMS spectra are then generated as where g , the g index, was originally taken as 13 63. Elsewhere, we show how the different monatomic primary ions may be ranked for their efficiency in generating G‐SIMS spectra 79. Good primary ions for the low d E /d x spectrum are Ar + , Ga + and Mn + and for the high dE/dx spectrum, Bi + and Au + , with Cs + , In + and Xe + being useful intermediate primary ions.…”
Section: G‐simsmentioning
confidence: 99%